IRAH-IRAHAN PAVILION: INTEGRATING SUSTAINABILITY AND INDONESIAN CULTURAL STORYTELLING THROUGH PAVILION BAMBOO DESIGN IN NANSHA BIRD PARK - Dara Citra Saraswati Tutuko; Rizal Qunaini; Krisna Wijaya Nagata; Tyastuti Cahyani Pancaputri; Ari Rifki Ramanda Putra; Anisatur Robi'ah; Pindo Tutuko (Architecture Study Program, Faculty Of Engineering, University of Merdeka Malang, 2025)
The Irah Irahan Pavilion is a sustainable bamboo structure designed to embrace Indonesia’s cultural heritage while integrating eco-friendly construction techniques. Inspired by Wayang, particularly the headpiece (Irah-Irah) of Gatotkaca, this pavilion symbolizes strength, resilience, and traditional craftsmanship. The design incorporates bamboo weaving (anyaman bambu) and active-bending techniques, allowing for a lightweight yet durable form that minimizes material waste. Located in Nansha Bird Park, the pavilion harmonizes with its natural surroundings, enhancing the visitor experience while promoting environmental consciousness. The project explores bamboo’s structural potential, utilizing modular assembly and efficient construction methods to ensure sustainability and adaptability. Through the fusion of cultural symbolism, and ecological responsibility, the Irah Irahan Pavilion demonstrates the potential of bamboo construction in creating aesthetic, functional, and environmentally sustainable design.